Peran Dukungan Keluarga Terhadap Pola Hidup Sehat dan Perilaku Pencegahan Stroke Pada Pasien Hipertensi: A Cross-Sectional Study - Udani, Giri; Murhan, Al; Riyanto, Riyanto (Yayasan Jompa Research and Development, 2025)
Hypertension is a major risk factor for cardiovascular disease and stroke, whose prevalence continues to increase i including in Indonesia. However, low patient adherence to a healthy lifestyle and preventive measures for complications still constrains efforts to control hypertension. Family support is a key factor that can enhance the effectiveness of hypertension management. This study aims to describe the effect of family support on healthy lifestyle and stroke complication prevention behaviors in hypertensive patients in an urban Indonesian community. This study used a descriptive quantitative approach with a cross-sectional design. We collected data from 100 adult hypertensive patients using a standardized questionnaire and a consecutive sampling technique. We collected data through interviews using a semi-structured instrument. We analyzed the data using descriptive statistics and a chi-square test at a probability level of 0.005. One hundred respondents, more than half (51%), gave poor support to hypertensive patients, and there was a significant relationship between family support and lifestyle in hypertensive patients (OR 2.882; CI 95% 1.275–6.515, p-value 0.018) and the relationship between family support and stroke prevention behavior in hypertensive patients (OR 3.875; CI 95% 1.678–8.947, p-value 0.002). Family support is important in improving healthy lifestyle adherence and complication prevention measures in hypertensive patients. These findings support the need to strengthen family-based interventions in the primary healthcare system in Indonesia.